Acute and Chronic Pathological Effects of Sulfur Mustard on Genitourinary System and Male Fertility - Panahi, Yunes; Ghanei, Mostafa; Ghabili, Kamyar; Ansarin, Khalil; Aslanabadi, Saeid; Poursaleh, Zohreh; Eslam Jamal Golzari, Samad; Etemadi, Jalal; Khalili, Majid; Mohajel Shoja, Mohammadali (Urology Journal, 2013)